Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Kemampuan Literasi Matematis Siswa Madrasah Aliyah pada Materi Barisan Ditinjau Dari Self Resilience - Naras; Nur Hardiani; Sofyan Mahfudy (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students’ mathematical literacy skills in the topic of sequences, viewed from self-resilience. This research employed a quasi-experimental method with a pretest–posttest nonequivalent control group design using a 2×3 factorial arrangement. The research sample consisted of an experimental class and a control class at MA Plus Nurul Islam Sekarbela. The research instruments included a mathematical literacy test, a self-resilience questionnaire, and observation sheets. Data were analyzed using the Independent Sample t-test and two-way ANOVA. The results showed that the Problem Based Learning (PBL) model had a significant effect on students’ mathematical literacy skills. The mean posttest score of the experimental class was higher than that of the control class. Meanwhile, self-resilience did not have a significant effect on mathematical literacy skills. Similarly, there was no significant interaction between the learning model and self-resilience. However, descriptively, students who learned through the Problem Based Learning (PBL) model showed higher mathematical literacy skills across all self-resilience categories compared to those in conventional learning. Based on the findings, it can be concluded that the Problem Based Learning (PBL) model effectively improves students’ mathematical literacy skills on sequences material, while self-resilience and its interaction with the learning model do not have a significant effect.